Dekolonialisasi dalam Geguritan Kebo Tarunāntaka: Representasi Kebo Taruna dalam Rekonstruksi Egalitarianisme - Paramita, Ida Bagus Gede (Jayapangus Press, 2025)
Kebo Taruna, within the discursive construction of centrality in shaping various aspects of Balinese society, possesses an inherent connection to the concept of representation. The ideational conception of this character is specifically conveyed in the Geguritan Kebo Tarunāntaka. The manuscript contains discourse mechanisms, metaphorical language, and distinctive constructions of meaning. Textually, the geguritan illustrates Kebo Taruna’s role in de-hegemonizing the dominance of the Majapahit Kingdom over the Balinese Kingdom. This study aims to identify the emancipatory dimensions of the Kebo Taruna character in selected stanzas of the Geguritan Kebo Tarunāntaka, to analyze his representation as a symbol of resistance against Majapahit’s hegemonic power, and to reinterpret the geguritan as a medium of decolonial discourse. The approach employed combines Norman Fairclough’s model of Critical Discourse Analysis (CDA) with speech act theory. The findings indicate that Kebo Taruna is represented as a symbolic agent who articulates resistance to the coloniality of power and constructs a sovereign and autonomous Balinese identity. The gegugitan reveals emancipatory dimensions through its rejection of hegemonic narratives, glorification of sovereignty, and transformation of language into a decolonial instrument. The conclusion affirms that Geguritan Kebo Tarunāntaka is not merely a literary heritage, but a discursive medium that embodies symbolic resistance, articulates a liberated cultural identity, and enacts decolonial strategies through language making it highly relevant for critical readings of power discourse within the Balinese local context.